2013
DOI: 10.3390/ijms140917553
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dopamine Receptors, Oxidative Stress, and Hypertension

Abstract: Dopamine, which is synthesized in the kidney, independent of renal nerves, plays an important role in the regulation of fluid and electrolyte balance and systemic blood pressure. Lack of any of the five dopamine receptor subtypes (D1R, D2R, D3R, D4R, and D5R) results in hypertension. D1R, D2R, and D5R have been reported to be important in the maintenance of a normal redox balance. In the kidney, the antioxidant effects of these receptors are caused by direct and indirect inhibition of pro-oxidant enzymes, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 137 publications
(187 reference statements)
5
66
0
Order By: Relevance
“…Antioxidants regulated by Nrf2, other than D 2 R and DJ-1, such as HO-1 could be involved in the antioxidant mechanism of DJ-1 and D 2 R. However, we have reported that the antioxidant effect of D 2 R is not related to HO-1 but rather due, in part, to HO-2 (5). Therefore, D 2 R stimulation increases the expression of some antioxidants such as HO-2 (7), PON2 (10), and DJ-1(11), independently of Nrf2 (Figure 6). …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Antioxidants regulated by Nrf2, other than D 2 R and DJ-1, such as HO-1 could be involved in the antioxidant mechanism of DJ-1 and D 2 R. However, we have reported that the antioxidant effect of D 2 R is not related to HO-1 but rather due, in part, to HO-2 (5). Therefore, D 2 R stimulation increases the expression of some antioxidants such as HO-2 (7), PON2 (10), and DJ-1(11), independently of Nrf2 (Figure 6). …”
Section: Discussionmentioning
confidence: 96%
“…Deletion of any of the dopamine receptor genes in mice results in increased blood pressure by mechanisms that are dopamine receptor subtype-specific (4). In particular, D 2 −/− and D 5 −/− mice have hypertension that is associated with oxidative stress (5,6,7). …”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is well known as a neurotransmitter. However, dopamine can regulate other cellular functions, including ion transport, smooth muscle contractility, hormone production, and cell proliferation (7)(8)(9). Dopamine can also regulate inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report that demonstrates the role of sestirn2 in the regulation of blood pressure. The increase in renal ROS production, associated with activation of the adrenergic nervous system and intrarenal renin-angiotensin system (RAS), may affect renal sodium transport causing sodium and fluid retention and ultimately hypertension [9, 14, 33]. Interestingly, we found that sestrin2 silencing increased hyper-oxidized peroxiredoxins in human PRTCs.…”
Section: Discussionmentioning
confidence: 90%
“…ROS production is limited not only by decreased oxidant activity, but also by increased antioxidant defense [10, 14]. Peroxiredoxins are thiol-based antioxidant enzymes detoxifying ROS by oxidation of their two cysteine groups to cysteine sulfinic acid (Cys-SO 2 H) or cysteine sulfonic acid (Cys-SO 3 H), causing inactivation of peroxidase activity [1619].…”
Section: Introductionmentioning
confidence: 99%